Pelatihan Pembudidayaan Dan Pemanfaatan Sirih Merah (Piper Crocatum) Menjadi Minuman Herbal - Fonny Rianawati; Muhammad Naparin; Muhammad Helmi (Jurnal Pengabdian ILUNG (Inovasi Lahan Basah Unggul), 2023)
It has been almost six months that Indonesia has been shocked by the outbreak of the corona virus (Covid 19) which is characterized by illnesses ranging from mild ones such as the common cold to severe ones such as Severe Acute Respiratory Syndrome (SARS). Red betel is a vine that can be planted in the yard of the house which is beneficial to the human body, because of its medicinal properties and the beauty of the leaves. The objectives of this Student Creativity Program are 1) How to cultivate red betel plants; 2) How to process red betel leaves into herbal drinks and 3) How to educate and motivate people to like these herbal beverage products to increase their body's resistance and immunity. The tools used in this study included dried and fresh red betel leaves, glasses, red betel cuttings, pots, organic fertilizer, sponge/cork, basin, and camera. The results of this technical guidence activities are in the form of 1) Herbal beverage products from red betel leaves, both in liquid and powder forms; 2) Red sirh puppies resulting from cultivation; 3) There is an increase in the skills of the community to utilize their yards by planting medicinal plants that are beneficial to increase endurance during the covid-19 pandemic. The results of this technical guidence, in addition to personal needs, can also be sold and used by other people so that they can increase family income. The technical guidence ran smoothly and the community enthusiastically participated in the whole series of activities marked by their active response to the material presented. Keywords: red betel leaves, herbal beverage, covid-19.